2013
DOI: 10.1103/physrevd.87.123532
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional reduction in the sky

Abstract: We explore the cosmological implications of a mechanism found in several approaches to quantum-gravity, whereby the spectral dimension of spacetime runs from the standard value of 4 in the infrared (IR) to a smaller value in the ultraviolet (UV). Specifically, we invoke the picture where the phenomenon is associated with modified dispersion relations. With minimal assumptions, we find that UV behaviour leading to 2 spectral dimensions results in an exactly scale-invariant spectrum of vacuum scalar and tensor f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
235
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(247 citation statements)
references
References 47 publications
(80 reference statements)
10
235
2
Order By: Relevance
“…They in fact describe effects that are quite generically expected in quantum gravity research [3,4] (and in particular have been explicitly shown to characterize 3D quantum gravity [5,6]) without introducing preferred frames and so evading the strong constraints on Lorentz invariance violations. Modified dispersion relations could produce observable phenomenology in the context of astrophysics [7][8][9][10][11] and there is also increasing evidence that they could be relevant in the early Universe [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They in fact describe effects that are quite generically expected in quantum gravity research [3,4] (and in particular have been explicitly shown to characterize 3D quantum gravity [5,6]) without introducing preferred frames and so evading the strong constraints on Lorentz invariance violations. Modified dispersion relations could produce observable phenomenology in the context of astrophysics [7][8][9][10][11] and there is also increasing evidence that they could be relevant in the early Universe [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that the method of introducing the effects of dimensional reduction applied here differs from the one considered in Ref. 8. In that reference, modified dispersion relation has been introduced at the level of timedependent speed of propagation.…”
Section: ∂ω(P) ∂Pmentioning
confidence: 99%
“…Therefore, we can immediately conclude that this universe is singular. c It is intriguing to observe that the UV value of the equation of state parameter matches the one of a radiation fluid in two spacetime dimensions, which is also the value of the UV spectral dimension that can be deduced from the dispersion relation (11) 10 . …”
Section: First Examplementioning
confidence: 99%